Factors influencing employee engagement: a study among production employees of TROX Malaysia Sdn Bhd / Nor Husna Shazween Abdul Rahim - Abdul Rahim, Nor Husna Shazween (Faculty of Business and Management, 2019)
Employee engagement has taken a vital role in today modern business world as a main issue for better employee and organizational success. A great deal of interest has been exposed in recent years. The purpose of this study was to examine the influential factors on employee engagement in manufacturing industry. A total of 122 questionnaires distributed to the respondent, however only 98 respondents completed and returned their questionnaires. The sampling design that was used in this research is non-probability convenience sampling. Based on a quantitative research method, data were collected for this study through a self-administered questionnaire survey, measured by five likert scale. Moreover, the result has shown that work-life balance and work environment has a significant relationship with employee engagement. While employee voice is not significant with employee engagement. The study findings indicated that work environment as the most influential factor on employee engagement among production employees of TROX Malaysia.